-x²-1supra lui x²+4x+4÷x+1supra lui x+2
Răspunsuri la întrebare
Răspuns de
0
(-x²-1)/(x²+4x+4) :(x+1)/( x+2)=
=(-x+1)(-x-1)/(x+2)² * (x+2)/(x+1)=
=-(-x+1)(+x+1)/(x+2) * 1/(x+1)=
=-(-x+1)/(x+2) * 1/1=
=(x-1)/(x+2)
=(-x+1)(-x-1)/(x+2)² * (x+2)/(x+1)=
=-(-x+1)(+x+1)/(x+2) * 1/(x+1)=
=-(-x+1)/(x+2) * 1/1=
=(x-1)/(x+2)
Alte întrebări interesante
Franceza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Fizică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă